Geodynamics of the Indosinian orogeny between the South China and Indochina blocks: Insights from latest Permian- Triassic granitoids and numerical modeling - Liu, H.; Wang, Y.; Li, Z.; Zi, Jianwei; Huangfu, P. (Geological Society of America, 2018)
The Indosinian orogeny experienced multiple subduction-collisional events along the Jinshajiang-Ailaoshan-Song Ma tectonic zone in response to closure of the Paleotethyan Ocean/back-arc basin, but the associated geodynamic processes are still poorly understood. Granitic rocks are the most common magmatic products in collisional orogens, and they can provide important information about orogenic geodynamics. In this study, three stages of collision-related igneous activity were identified along the Jinshajiang- Ailaoshan-Song Ma suture zone: (1) Latest Permian to earliest Triassic (ca. 255-248 Ma) high-eHf(t) and high-eNd(t) I-type granites, low-eNd(t) and low-eHf(t) I-type granites, and S-type granites; (2) Early to Middle Triassic (247-237 Ma) S-type leucogranites and high- Si peraluminous rhyolites; and (3) Late Triassic (ca. 235-202 Ma) high-eNd(t) and high- eHf(t) I-type granites, low-eNd(t) and low-eHf(t) I-type granodiorites, and S-type granites. A synthesis of the data for the latest Permian to Triassic magmatic and coeval high-pressure and ultrahigh-pressure metamorphic rocks suggests a three-stage model for the convergence between the Simao-Indochina and South China blocks. Termination of arc magmatism and commencement of continental collision occurred in the latest Permian-earliest Triassic (ca. 255-248 Ma), followed by continental subduction in the Early to Middle Triassic (247-237 Ma) and Late Triassic postcollisional slab breakoff and conticontinental exhumation (ca. 235-202 Ma). A two-dimensional high-resolution numerical model reproduced this evolutionary process and revealed the lateral structural heterogeneity of the subducting and overriding plates during the Indosinian orogeny.